1st. International Conference on Sports and Exercise Science 2009 Bangkok, Thailand 01-03 Disember 2009 - Hamzah, Nurul Azuar (Universiti Sains Malaysia, 2012)
EFFECTS OF SOUND AIDED IMAGERY TRAINING ON PERFORMANCE SCORE, HEART RATE AND PERCEIVED STATE ANXIETY IN KELANTAN STATE BOWLING ATHLETES